2018
DOI: 10.18843/ijcms/v9i2/04
|View full text |Cite
|
Sign up to set email alerts
|

Buying Insurance Online: Are we there yet?

Abstract: The study has been undertaken with the objective of identifying the factors that influences the online channel adoption intent of the customers for the financial products and to zero in on the segment that is interested in the online channel by combining the identified factors with the demographic and behavioural variables of the customers. New variables had been introduced for the study along with using the variables from existing literature. Exploratory factor analysis had been carried out and 9 factors had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, these authors found an insignificant relationship between behavioral attention and service attributes. Based on TAM, Maheswari and Chandrasekaran [11] discovered that perceived benefits and technological attributes play a critical role in leading consumers to adopt online insurance.…”
Section: Antecedents Of Online Insurance Adoptionmentioning
confidence: 99%
“…However, these authors found an insignificant relationship between behavioral attention and service attributes. Based on TAM, Maheswari and Chandrasekaran [11] discovered that perceived benefits and technological attributes play a critical role in leading consumers to adopt online insurance.…”
Section: Antecedents Of Online Insurance Adoptionmentioning
confidence: 99%
“…However, e-insurance services have been reluctant to gain traction, with many customers mainly selecting traditional insurance services. This article explores the elements that influence Indian customers' acceptance of e-insurance (Maheswari, & Chandrasekaran, 2018). E-insurance services have arisen as a paradigm shift in the insurance sector, allowing users to buy and manage insurance plans online.…”
Section: Introductionmentioning
confidence: 99%